Effectiveness of Dexmedetomidine Compared to Midazolam for Sedation in Mechanically Ventilated Patients: A Narrative Review - Haithami, Guntur Mu Ammar; Putu Agus Surya Panji; Ida Bagus Krisna Jaya Sutawan; Christopher Ryalino (Jurnal Anestesiologi dan Terapi Intensif, 2025)
Delirium is a common and clinically significant neuropsychiatric complication in mechanically ventilated adult ICU patients, contributing to prolonged hospitalization, increased morbidity, and long-term cognitive impairment. The choice of sedative agent plays a pivotal role in preventing delirium, with dexmedetomidine and midazolam representing the most commonly used drugs with contrasting mechanisms. This narrative review evaluates the clinical efficacy, safety profile, neurocognitive outcomes, and cost-effectiveness of dexmedetomidine compared with midazolam in mechanically ventilated ICU patients. Literature was searched through PubMed, Scopus, ScienceDirect, Cochrane Library, and Google Scholar for studies published between 2020 and 2025 using the keywords dexmedetomidine, midazolam, sedation, mechanical ventilation, delirium, and intensive care units. Seventeen peer-reviewed publications were included and analyzed narratively. Dexmedetomidine consistently reduced the incidence and duration of delirium (RR 0.55–0.65; 95% CI 0.4–0.8), shortened mechanical ventilation by 0.7–1.5 days, and facilitated earlier extubation compared to midazolam. Its α₂-adrenergic agonism at the locus coeruleus produces a sleep-like, cooperative sedation, with mild, dose-dependent bradycardia as the most frequent adverse effect. Despite higher acquisition cost, economic analyses reported average savings of US$ 450–700 (≈ IDR 7–10 million) per patient through reduced ICU stay and delirium-related complications. Overall, dexmedetomidine demonstrates superior efficacy and safety compared with midazolam for ICU sedation, providing both clinical and economic advantages. Integration into light-sedation and delirium-prevention bundles may improve ICU outcomes, particularly in resource-limited settings.